Mengajarkan Gaya Hidup Sehat Sejak Dini Dengan Metode Bercerita Pada Siswa SDN 34 Air Pacah Kec. Koto Tangah, Kota Padang - Cut Sarha Airlangga; Osami Putri Anelta (PUSAKO : Jurnal Pengabdian Psikologi, 2022)
A healthy lifestyle is basically a person's response to stimuli related to food, personal hygiene, environmental hygiene, habits against illness and disease and a balance between work, rest and exercise. However, the reality of a healthy lifestyle for SDN 34 Air Pacah students has not been fully realized properly. This can be seen from the many problems of students who have not implemented a healthy lifestyle such as washing hands before eating, smoking, consuming nutritious food and getting enough rest. Thus, information is needed regarding healthy lifestyles for students of SDN 34 Air Pacah. By using methods in the form of stories, FGD, ice breaking, and evaluation to implement a healthy lifestyle in order to produce good behavior and can be applied by students of SDN 34 Air Pacah Padang City. This activity was carried out on January 19 to January 25, 2022 in grades 4, 5 and 6 of SDN 34 Air Pacah Padang City. The results of this activity show the application of a healthy lifestyle in educating students regarding the importance of a healthy lifestyle. Kewyords : Healthy lifestyle; storytelling method; elementary school students.